The realization of prosodic categories in political media discourse in British and American linguacultures - L. V. Milyaeva (Дискурс профессиональной коммуникации, 2020)
The main aim of the article is to describe, analyze and compare main prosodic categories that are realized in a unique context, namely in political media discourse. The article looks into the principles of classification of the prosodic categories as well as at realizational differences of three main prosodic categories: syllable, foot and intonation phrase. These categories are distinguished unanimously by the majority of the researchers and are described in the article form their structural and cognitive perspectives. The realizational differences of these categories derive from pragmatic and linguacultural features of English media communication. In the article media communication is represented with political media discourse which is understood as a new contextual model of media communication and is characterized by high degree of immediacy and interactivity. Certain attention in the article is given to the results of the comparative research of the realizational differences of the prosodic categories done by the author. On the basis of the data resulted from the prosodic and content analysis the author concludes that the realizational differences of the prosodic categories are often due to pragmatics of the discourse and the type of discourse itself.